The principle of Sustainable Development in International Legal Acts and Judicial Practice of the International Court of Justice - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The aim of this paper is to present how the regulation of sustainable development on the international level. The sustainable development was defined in the middle of 1980s and from that moment it incites discussions among lawyers about its relevance in international law. Some authors state that it is not a fully formed principle but that it is in the process of creation. The exception from this opinion is the position of the Judge Weeramantry in the Case Gabčíkovo-Nagymaros before the International Court of Justice. Since it is a principle, it does not contain clearly defined rights and duties but it is formulated generally and even vague regarding its legal effects. However, it is a legal principle which, contrary to moral or political principles, has binding legal effects and cannot be neglected. It is contained in several international treaties and it is also a part of the European Union Law. The principle of sustainable development is connected with the precautionary principle, environmental impact assessment and other principles.